Epidemiological and Clinical Characteristics of Respiratory Syncytial Virus Infection in Children in Hangzhou (2022–2023) - Lai, Qin-Rui; Chu, Xiao-Li; Chen, Ying-Ying; Li, Wei; Guo, Ya-Jun; Shang, Shi-Qiang (Pathogens (Basel), 2025)
Human respiratory syncytial virus (HRSV) is a highly contagious RNA virus that causes respiratory infections, especially in children. This study evaluated the impact of COVID-19 control measure changes on HRSV infection patterns in Hangzhou by comparing epidemiological and clinical characteristics. We conducted a retrospective analysis of 12,993 pediatric nasopharyngeal swab samples from children with acute respiratory infections at The Children’s Hospital of Zhejiang University School of Medicine. These samples, collected between February 2022 and January 2024, were screened for HRSV and 12 other respiratory pathogens using capillary electrophoresis technology. From February 2022 to January 2023, the HRSV positivity rate was 7.06%. In 2023, it increased to 9.26%. The highest positivity rates were in infants aged 0–6 months and children aged 6 months to 1 year. Coinfections were most common with rhinovirus in 2022 and Mycoplasma pneumoniae in 2023. HRSV positivity rates were low from April to September 2022, peaking in December. In 2023, the peak occurred from April to September. Symptoms ranged from mild to severe pneumonia, with higher hospitalization rates in children with underlying conditions. The study revealed significant changes in HRSV infection rates following pandemic restriction relaxations, emphasizing the need for the early identification and prevention of severe cases.